Investigation of mixing in binary surfactant solutions by surface tension and neutron reflection: Anionic/nonionic and zwitterionic/nonionic mixtures - Hines, J; Thomas, R; Garrett, P; Rennie, G; Penfold, J (1997)
Surface tension and neutron reflection measurements have been used to study the surface composition of aqueous solutions of mixtures of sodium dodecyl sulfate (SDS) and n-dodecyl-β-D-maltoside (C12maltoside) and C12maltoside and n-dodecyl-N,n′-dimethylamino betaine (C12betaine). From measurements of surface tension and mixed critical micelle concentrations (cmc) the pseudo-phase separation model has been used to calculate values of the interaction parameters in the micelle, βM, and at the surface, βσ. SDS/C12maltoside mixtures behave nonideally and both βM are negative, indicating attractive interactions between the two surfactants, but the C12maltoside/C12betaine mixtures are closer to being ideal. Direct measurements of the surface excess using neutron reflection on isotopic mixtures of the surfactants are shown to be consistent with the surface tension measurements using the integrated form of the Gibbs equation. These direct values of the surface excess were found to agree with predictions from the partial phase separation model in the case of the nonideal pair, SDS/C12maltoside, but were different for the ideal pair, C12maltoside/C12betaine. It is suggested that this may result from the relatively large errors in the partial phase separation model when the mixture is very unsymmetrical (very different cmc's coupled with weak interaction). The C12maltoside/ C12betaine mixture was found to behave regularly in that βσ showed negligible variation with either surface pressure or composition. On the other hand for the nonideal pair, SDS/C12maltoside, the magnitude of βσ decreased with surface pressure, consistent with reduced interaction as the molecules are more widely spaced, and also decreased with higher SDS fraction in the layer, consistent with an increasing contribution from electrostatic repulsion.